Analysis and Design of Human Resource Information System at PT. Jasamitra Propertindo - Novita Kurniasari; Sri Hariani Eko Wulandari; Rudi Santoso (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Part Persoalia PT. Jasamitra Propertindo have HR management tasks include human resource planning, employee recruitment, employee selection, placement and orientation, training and development, performance appraisal, and termination of employment. In the daily implementation of all human resources management tasks created manually. Therefore, the company wants the Human Resource Information System. The obstacles, the current PT. Jasamitra Propertindo not know the needs of the system according to the needs of Personnel.The solution offered is to do a needs analysis and design of Human Resource Information System capable of handling ranging from human resource planning, employee recruitment, selection, training and development, placement and orientation, performance assessment, until the termination of employment with the effective, efficient and accurate.The result of this research is the formulation of system requirements analysis, system design, system design and evaluation. After the evaluation, the draft document human resources information system at PT. Jasamitra Propertindo able to produce systems that help the company in the process of managing the company, especially in the human resources department.